Comparison of the Effectiveness of Finger Grip and Lavender Aromatherapy on Changes in Pain Post - Apendectomy - Fadli Fadli; Eko Winarto; Yunani Yunani; Fery Agusman (Media Publikasi Cendekia Indonesia, 2026)
Post-appendectomy pain, caused by tissue trauma and inflammation, significantly impedes patient recovery and highlights the need for effective, non-pharmacological interventions to complement standard analgesics. This study aimed to evaluate and compare the effectiveness of Finger Grip Relaxation and Lavender Aromatherapy in reducing pain intensity among post-appendectomy patients. A quasi-experimental pretest-posttest design with two groups was conducted involving 30 adult patients (aged 18–65 years) at dr. H. Jusuf SK Tarakan Regional General Hospital. Participants were selected using purposive sampling and assigned to either the Finger Grip Relaxation group (n = 15) or the Lavender Aromatherapy group (n = 15). Each intervention was administered for 30 minutes daily over two consecutive days. Pain intensity was measured using the Numeric Rating Scale (NRS; 0–10). Due to non-normal data distribution confirmed by Shapiro–Wilk tests, data were analyzed using the Wilcoxon signed-rank test for within-group changes and the Mann–Whitney U test for between-group comparisons (α = 0.05). Both interventions yielded a statistically significant reduction in post-appendectomy pain. In the Finger Grip Relaxation group, the mean NRS score decreased from 6.60 to 4.20 (p = 0.001). In the Lavender Aromatherapy group, the mean NRS score decreased from 7.60 to 4.27 (p = 0.001). The Mann–Whitney U test revealed a significant difference in pain reduction between the two groups (p = 0.012), indicating that Lavender Aromatherapy produced a greater decrease in pain intensity. Descriptive analyses confirmed no significant differences in baseline characteristics (age, sex, and health history) between the groups. Both Lavender Aromatherapy and Finger Grip Relaxation serve as promising complementary options for post-appendectomy pain management. However, Lavender Aromatherapy demonstrated superior efficacy in pain reduction within this small-scale study. Future studies with randomized controlled designs and larger sample sizes are recommended to validate these preliminary findings